Pengaruh Media Buku Teks Terhadap Hasil Belajar Siswa Kelas V SDN Bandung 1 Jombang - Siti Roudhotul Jannah; Muhammad Nuruddin (Jurnal Simki Postgraduate, 2025)
Educators at SD Negeri Bandung 1 Jombang continue to underutilize instructional material throughout the teaching process, leading to students' academic performance failing to meet the Minimum Completeness Criteria (KKM) established by the institution. Furthermore, the pupils exhibit less enthusiasm and motivation in the educational process, adversely affecting their comprehension and diminishing the anticipated learning outcomes. Consequently, an educator must select the suitable media for use throughout the learning process. The utilization of educational media significantly enhances the learning process; it enables educators to more effectively communicate instructional content and aids students in comprehending the material offered. Textbooks serve as an effective educational medium because to its engaging pictures and accessible language, which facilitate comprehension for primary school children, hence enhancing their learning results. This study aims to evaluate how specially designed textbook materials impact the academic achievement of fifth-grade students at SD Negeri Bandung 1 Jombang when learning the IPAS subject Getting to Know Our Earth. The used research design is the one-group pretest-posttest. There are twenty fifth graders among the research subjects. The p-value of 0.000 from the paired sample t-test indicates statistical significance (p < 0.05). Therefore, we can conclude that the specially designed textbook media has a significant effect on student learning outcomes.